Analysis of crimes in metropolitan cities of India - Rambooshan Tiwari (National Geographical Journal of India, 2022)
Crime is a social problem that disturbs the peace and tranquillity of society. It can be inferred from the National Crime Record Bureau (NCRB) data that urban areas, particularly metropolitan cities, are more prone to crime in comparison to their rural counterparts. As per the 2011 census, about 13% population of the country is residing in metropolitan cities while their contribution to total crime incidents was about 28% in 2015.Apositive correlation (+0.69) between city size and the crime rate is also recorded during the reference year. Fifty-three metropolitan cities reported in the 2011 census are facing a differential rate of crime. National Crime Record Bureau (NCRB) publishes year-wise data of crime in India, which also contain data of all metropolitan cities. Based on NCRB data, the incidents and rate of IPC crimes, violent crimes, and the crime against women in metropolitan cities are analyzed in the study. It is found that metropolitan cities of northern and central India having a higher rate of crime in comparison to other cities. The nature of crime also varies considerably in these cities as incidents of violent crime and crime against women are disproportionately high in the cities of Hindi speaking states. Many relatively small metropolitan cities have a comparatively higher rate of IPC crimes, violent crimes, and crimes against women. The impact of metropolitan cities on the total crime of their respective states has been analyzed, and it is evident that in many states, particularly central Indian states, crime is highly concentrated in metropolitan cities.